1998
DOI: 10.1159/000017072
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Electroencephalography and Regional Cerebral Blood Flow: Discriminant Analysis between Alzheimer’s Patients and Healthy Controls

Abstract: Forty-two patients with probable Alzheimer’s disease (AD) and 18 elderly healthy controls underwent quantitative EEG (qEEG) and regional cerebral blood flow (rCBF; 133Xe clearance) examinations. Correlations were sought between relative qEEG band powers and percent rCBF values in a posterior temporoparietal region of interest in either hemisphere. Moreover, stepwise discriminant analysis was applied to study the accuracy of the two techniques in differentiating AD from healthy ageing. rCBF and qEEG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 48 publications
4
43
0
2
Order By: Relevance
“…The possible involvement of hippocampus is further supported by the correlation of medial temporal lobe atrophy and increase in neocortical theta activity in human studies [21]. Another mechanism associated with slowing of the EEG is progressive cortical hypoperfusion [36,46], where disturbed connections in autoregulation or regulation from deeper areas on vessels could be a possible contributor.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The possible involvement of hippocampus is further supported by the correlation of medial temporal lobe atrophy and increase in neocortical theta activity in human studies [21]. Another mechanism associated with slowing of the EEG is progressive cortical hypoperfusion [36,46], where disturbed connections in autoregulation or regulation from deeper areas on vessels could be a possible contributor.…”
Section: Discussionmentioning
confidence: 95%
“…Hippocampal atrophy on MRI [21], abnormal cerebral blood flow [36,46], autopsy-confirmed neuron loss [45], activity of daily living functions [39] and memory function [44,57] have all correlated with slowing of EEG rhythm. Furthermore, a previous study reported a correlation between tau protein and slowing of EEG global field 5 power in a healthy control group [28].…”
Section: Introductionmentioning
confidence: 99%
“…Recent data [39] comparing rates of glucose metabolism with that of [ 11 C]methionine accumulation, as measured by PET, support the view that tissue loss alone cannot explain the glucose hypometabolism of AD patients, which may actually reflect reduced synaptic activity at least in part. By reflecting tissue loss and probably synaptic dysfunction as well, metabolic and blood flow measurements are significantly related to the severity of the disease [21,40,41] and then may be expected to be linked with disease progression as well.…”
Section: Discussionmentioning
confidence: 99%
“…There were 69 women and 32 men, aged 45-91 years (mean 70.1 B 8.7 years) with apparent duration of disease (determined as onset of first symptoms referred by the patient or his/her relatives) ranging from 6 to 108 months (mean 32.1 B 24 months). All patients underwent a complete diagnostic workup according to the current clinical standards, as already described in detail elsewhere [21]. Consistent with the diagnosis of AD, all of them scored lower than 4 on the modified Hachinski Ischemic Scale.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation